Fabrication and Characterization of Core Offset Waveguide Optical Sensor for Refractive Index Measurement - Dhea Paradita; Ian Yulianti; Mei Suhantoro (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2022)
Refractive index is important parameter in various fields, such as environmental, chemical, industrial, and medical. Measurement of refractive index can be done using optical sensor based buried waveguide core offset. This research aims to fabricate and characterize core offset buried waveguide based on Polymethyl Methacrylate (PMMA).  Fabrication of buried waveguide was done by creating a cladding of waveguide made from PMMA which has a refractive index of 1.4908 using computer numerical Control machine  (CNC). The material used as waveguide core was unsaturated polyester resin (UPR). Characterization was performed to determine the spectrum of input intensity and output intensity.  Characterization were done by dipping the waveguide sample in to a container containing glucose solution with concentration of 12%, 14%, 16%, 18%, 20%, and 24%. Waveguide was connected to Polymer Fiber Optic (POF). One of the of POF as an input is connected to light emited diode with wavelength of 470 nm and one of the end other POF as an output was connected to Spectrometer Ocean Optic USB4000. The result showed that the total loss at concentration of 12%-24% is -4.62 dB, -5,70 dB, -6,01 dB, -6,49 dB, -6,15 dB, -6,16 dB, respectively. Sensor works well at a solution concentration of 16%-20% with a sensitivity value of 19.62 dB/RIU and correlation factor of 92.76%.